Development of three-year old Nigerian numerical child dummy model for vehicle safety assessment - Rafukka, Ibrahim Abdullahi (2017)
Child injuries in vehicular crashes especially on the head, is considered a major public health problem worldwide. Biofidelic child dummy is a key to designing safer vehicle to child occupants. Current crash dummies used for the evaluation of vehicle safety performance were developed based on 50th percentiles of some specific populations of the world. Biomechanical response of child occupant on crash depends on the size and weight; Nigerian children need crash dummy model with biofidelic head representing their own anthropometry for crash test of vehicle used by this vulnerable population. The aim of this work is to develop three year old Nigerian child dummy model that can predict injuries from various head locations for application in vehicle crash test. In the present work, anthropometric comparison was conducted where significant difference was found between the three year old Nigerian child (3YO NC) and current three year old Hybrid III (3YO HIII) and Q3s dummies with a maximum difference of more than 25% in body dimensions. To develop dummy for 3YO NC anthropometry, morphing technique in LS-DYNA software was used. It was first verified by developing a 3YO HIII dummy finite element (FE) model using six year old Hybrid III (6YO HIII) FE dummy model as a reference, and its biomechanical responses were compared with experimental and simulation results using physical 3YO HIII dummy from which it was found to be consistent both qualitatively and quantitatively. Detailed development of 3YO NC dummy model using the same scaling procedures was then accomplished. In this case, the body segments were morphed and material properties were modelled. The dummy head model was validated against the experimental data inferred from a nine year old child cadaver head recently published in literature for five impact locations namely; frontal, right and left parietals, vertex and occipital. The difference between child head FE model and scaled cadaver data is approximately 3% to 24%. The neck and thorax responses were also validated against three year old certification corridors, cadaver data and by comparison with other three year old child dummy models response available in the literature. The 3YO NC dummy response was found to be closer to certification corridors than the existing 3YO HIII dummy in some parameters. Other body parts were morphed and their material properties were modelled such that the weight fit that of 3YO NC. Comparison between morphed 3YO NC and morphed 3YO HIII in chest acceleration and upper neck moment and forces shows difference of approximately 6.5% to 41% between the two dummies. Finite element model of child restraint seat (CRS) was also developed and validated to accommodate the child model in crash simulations. Crash analysis was conducted in LS-DYNA software with newly developed Nigerian child dummy in CRS using the Ford Taurus 1992 FE model in order to evaluate its crashworthiness capability with respect to three year old child occupants. The three year old child injury parameters: Head Injury Criteria (HIC15, HIC36) and neck moment (NM) were found to be 47%, 49% and 85% respectively above the NHTSA threshold while upper neck force and chest deflection were found to be within an acceptable range. The technique employed in this study can be applied to develop dummy FE model of various sizes from existing crash dummy models. Biofidelic head model can be used to estimate injuries from vehicle crash due to contact of head with vehicle interior and height fall accidents for various head locations.